2014
DOI: 10.1007/s10875-014-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients with RAG Mutations Previously Diagnosed with Common Variable Immunodeficiency Disorders

Abstract: Purpose Combined immunodeficiency (CID) presents a unique challenge to clinicians. Two patients presented with the prior clinical diagnosis of common variable immunodeficiency (CVID) disorder marked by an early age of presentation, opportunistic infections, and persistent lymphopenia. Due to the presence of atypical clinical features, next generation sequencing was applied documenting RAG deficiency in both patients. Methods Two different genetic analysis techniques were applied in these patients including w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…Following this description, several other cases of CID–G/AI with various auto immune manifestations (such as cytopaenias, vitiligo, psoriasis, myasthenia gravis and Guillain–Barré syndrome) have been reported 3340 . Additional phenotypes that are associated with RAG deficiency include idiopathic CD4 + T cell lymphopaenia 41 , common variable immunodeficiency 40,42 , IgA deficiency 43,44 , selective deficiency of polysaccharide-specific antibody responses 44 , hyper-IgM syndrome 45 and sterile chronic multifocal osteomyelitis 46 . Overall, these observations have substantially broadened the clinical and immunological spectrum of human RAG deficiency and have identified immune dysregulation as a prominent manifestation of perturbed RAG function.…”
Section: Clinical Phenotype Of Rag Deficiencymentioning
confidence: 77%
“…Following this description, several other cases of CID–G/AI with various auto immune manifestations (such as cytopaenias, vitiligo, psoriasis, myasthenia gravis and Guillain–Barré syndrome) have been reported 3340 . Additional phenotypes that are associated with RAG deficiency include idiopathic CD4 + T cell lymphopaenia 41 , common variable immunodeficiency 40,42 , IgA deficiency 43,44 , selective deficiency of polysaccharide-specific antibody responses 44 , hyper-IgM syndrome 45 and sterile chronic multifocal osteomyelitis 46 . Overall, these observations have substantially broadened the clinical and immunological spectrum of human RAG deficiency and have identified immune dysregulation as a prominent manifestation of perturbed RAG function.…”
Section: Clinical Phenotype Of Rag Deficiencymentioning
confidence: 77%
“…Recent studies show that pulmonary lesions similar to GLILD can also occur in primary immunodeficiencies other than CVID, for example, cytotoxic T lymphocyte antigen-4 (CTLA4) deficiency, lipopolysaccharide responsive beige-like anchor protein (LRBA) deficiency and hypomorphic mutations in the recombinase-activating gene 1 (Rag1) [3740]. Importantly, hypogammaglobulinemia may be one of the immunological abnormalities found in these primary immunodeficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…The genes and the pathways identified in this study may be further pursued by studies with larger sample size and functional studies. In addition to whole genome-sequencing, recently exome-sequencing identified additional mutations that are related or causative in individual CVID patients, such as the newly identified mutations in genes NLRP12 [53], NFKB2 [54], ITPKB [55] and RAG1 [56]. A recent genetic study using whole exome-sequencing and comparative genomic hybridization array identified multiple heterozygous mutations and deletions in gene IKZF1 responsible for a form of CVID with drastically reduced number of B cells.…”
Section: Whole Genome Sequencing and Rna Sequencingmentioning
confidence: 99%